An unchosen people : Jewish political reckoning in interwar Poland - Moss, Kenneth B. (2021)
Conventional histories of modern Jewish politics emphasize the agency offered by Zionism, liberalism, and socialism. Kenneth B. Moss traces a darker reckoning with powerlessness amid grave dangers in Europe's largest Jewish community, recovering a search for realism about minority experience, the nation-state, and the making of a future.